Implementation of think pair share model to improve mathematics learning outcomes - Jose Bonatua Hasibuan (Inovasi Kurikulum, 2024)
The mathematics learning outcomes of students in class X APHP 1 SMKN Pertanian Terpadu Provinsi Riau in the 2022/2023 academic year show that the percentage of classical achievement is only 35.9 percent. From the reflection of the learning process carried out by the teacher, the following conclusions: (1) the learning process was still teacher-centered; (2) during the teaching and learning process, only a small number of students actively participated in the teaching and learning process; (3) there were still students who did not do their work and only copied their friends' work. This study aims to increase students' activity and learning outcomes by applying the Think Pair Share cooperative learning model. This type of research is Classroom Action Research with two cycles. The subjects of this study were 39 students of class X APHP 1 at the SMKN Pertanian Terpadu Provinsi Riau. The results showed that applying the TPS type of cooperative learning model can be active in learning outcomes, as seen by an increase from cycle I to cycle II. The number of students who achieved KKM in the first cycle was 79.5 percent, while in the second cycle, it was 89.7 percent. Therefore, the TPS-type cooperative learning model can be used as an alternative to learning mathematics to improve student learning outcomes. AbstrakHasil belajar Matematika peserta didik kelas X APHP 1 SMKN Pertanian Terpadu Provinsi Riau semester ganjil tahun ajaran 2022/2023 menunjukkan bahwa persentase ketercapaian secara klasikal hanya sebesar 35,9 persen. Dari hasil refleksi proses pembelajaran yang dilakukan guru diperoleh kesimpulan bahwa: (1) proses pembelajaran masih berpusat pada guru; (2) pada saat proses belajar mengajar berlangsung hanya sebagian kecil peserta didik yang melakukan aktif untuk berpartisipasi dalam proses belajar mengajar; (3) masih terdapat peserta didik yang tidak mengerjakan pekerjaannya dan hanya selalu meniru pekerjaan temannya. Penelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar peserta didik melalui penerapan model pembelajaran kooperatif tipe Think Pair Share (TPS). Jenis penelitian ini adalah Penelitian Tindakan Kelas dengan dua siklus. Subyek penelitian ini adalah 39 peserta didik kelas X APHP 1 SMKN Pertanian Terpadu Provinsi Riau. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif tipe TPS dapat aktivitas dan hasil belajar, terlihat dengan adanya peningkatan dari siklus I ke siklus II. Jumlah peserta didik yang mencapai KKM pada siklus pertama 79,5 persen, sedangkan pada siklus II 89,7 persen. Oleh karena itu, model pembelajaran kooperatif tipe TPS dapat dijadikan salah satu alternatif pembelajaran Matematika untuk meningkatkan hasil belajar peserta didik.Kata Kunci: hasil belajar; pembelajaran kooperatif; penelitian tindakan kelas; think pair share